Pelembagaan Participatory Poverty Assessment Sebagai Strategi Pengentasan Kemiskinan di Samigaluh Kabupaten Kulonprogo - Awang Darumurti (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
This article try to analysis strategy for reducing poverty in Samigaluh Municapy, Kulonprogo Region by using Participatory Poverty Assessment (PPA) strategy. PPA known as strategy to reduce poverty by including poor people to find solution of their poverty problem. In Other word, this strategy use bottom up method to reduce poverty. In Samigaluh, Poverty condition clearly seen as so many people live in near poor condition. This research use qualitative approach and data collect technic use interview and observation. From the research is gotten data that poor condition in Samigaluh caused by economic aspect, uncapability, isolation condition. PPA strategy, which is including poor people in solution making, give result that we must do some activities. The Activities are women empowernment, Informal institution empowernment, Increase Education, Training, and so on.